Biodistribution and toxicity of orally administered poly (lactic-co-glycolic) acid nanoparticles to F344 rats for 21 days. (July 2016) - Navarro, Sara M; Morgan, Timothy W; Astete, Carlos E; Stout, Rhett W; Coulon, Diana; Mottram, Peter; Sabliov, Cristina M
Aim: Quantify the biodistribution and assess the toxicity of PLGA (poly-lactic-co-glycolic acid) and surface-modified PLGA chitosan (PLGA/Chi) nanoparticles (NPs) orally administered for 7, 14 and 21 days to F344 rats.Materials & methods: Fluorescent NPs were tracked in F344 rat tissues, and toxicity was evaluated by alkaline phosphatase and alanine transaminase levels, and by histologic examination of tissue samples.Results: Biodistribution of PLGA and PLGA/Chi were similar, with highest amounts found in the intestine and liver. Alkaline phosphatase increased significantly in treated rats. Mild histological differences were detected in the intestine and liver.Conclusion: PLGA and PLGA/Chi NPs behaved similarly presenting minimal toxicity in the liver and intestine, but not in kidney, lung and brain.